Using human induced pluripotent stem cells to study the in vitro phenotype of the cardiac channelopathies - Duncan, Gary (2017)
Long QT Syndrome 2 (LQTS2) and Catecholaminergic Polymorphic Ventricular Tachycardia (CPVT) are two prevalent cardiac channelopathies. LQTS2 is the second most common form of LQTS and accounts for up to 45% of cases (Schwartz et al, 2012). CPVT1 is the most common form of CPVT and relates to dysfunction of the RYR2, mutations in RYR2 are thought to account for up to 50% of CPVT cases (Nyegaard et al, 2012). Treatment for these conditions is vital as mortality rates for untreated individuals can range from 21% to potentially as high as 50% (Leenhardt et al, 1995; Schwartz et al, 2012). Discovering novel compounds which treat these conditions is beset by suboptimal drug discovery methods which utilise animal models, which can be inaccurate due to inter-species variability in the cardiovascular system (Rajamohan et al, 2013), and heterologous overexpression systems which test the effect of a drug on specific ion channels which are limited by the inability of these systems to model the dynamic interaction between different ion channels in vivo (Kramer et al, 2013). Using human induced pluripotent stem cells (hiPSC) it is possible to generate cardiomyocytes which may enable the creation of humanised models of disease. Such models may enable the discovery of efficacious compounds more readily than current drug development techniques and they may also allow the study of disease pathogenesis in more detail than is currently available in human systems.